Implementasi Model Pembelajaran Role Playing dalam Meningkatkan Nilai Karakter Siswa Kelas X melalui Pembelajaran Pendidikan Pancasila di SMA Negeri 1 Tabanan - Agustyani Putri, Ni Putu Widya; Sujana, I Putu Windu Mertha; Utami, Anak Agung Istri Dewi Adhi (Ganesha Civic Education Journal, 2026)
Civics Education learning is still predominantly oriented toward theoretical content delivery, resulting in the suboptimal internalization of students’ character values. This condition necessitates the implementation of learning models that are more interactive, contextual, and capable of providing meaningful learning experiences for students. This study aims to analyze, evaluate, and interpret the implementation of the role-playing learning model in enhancing the character values of Grade X students. The study employed a qualitative approach with a descriptive–interpretative research design. The research subjects consisted of one principal, one vice principal for curriculum affairs, one Civics Education teacher, and 36 Grade X students. Data were collected through observation using observation sheets, semi-structured interviews guided by interview protocols, and documentation. Data analysis was conducted using descriptive qualitative techniques, including data reduction, data display, and conclusion drawing. The results indicate that the implementation of the role-playing model was carried out effectively and succeeded in enhancing students’ character values, particularly responsibility, cooperation, self-confidence, courage in expressing opinions, and critical thinking, in line with the main objectives of the study. In conclusion, the role-playing learning model is effective and relevant as a character-based instructional strategy in Civics Education. The findings imply that role playing can serve as an alternative learning model that supports the Merdeka Curriculum and the Pancasila Student Profile through active, reflective, and contextual learning.